Batteries: Homogeneous CoO on Graphene for Binder‐Free and Ultralong‐Life Lithium Ion Batteries (Adv. Funct. Mater. 35/2013). (17th September 2013) - Huang, Xiao‐lei; Wang, Ru‐zhi; Xu, Dan; Wang, Zhong‐li; Wang, Heng‐guo; Xu, Ji‐jing; Wu, Zhong; Liu, Qing‐chao; Zhang, Yu; Zhang, Xin‐bo
<x xml:space="preserve">Abstract</x> Y. Zhang, X.‐B. Zhang, and co‐workers report on page 4345 an electrostatic‐induced spread‐growth method to homogeneously coat CoO on graphene. Binder‐free electrode with excellent structural stability can then be easily prepared by layer‐by‐layer stacking. As an anode for Li‐ion batteries, the asprepared electrode exhibits a high rate capability and excellent cycle stability up to 5000 cycles. This opens up a promising strategy to develop high‐performance anodes for next‐generation LIBs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>